TEST OF ANTIOXIDANT ACTIVITY (DPPH METHOD) OF METHANOL EXTRACT AND ITS FRACTIONS FROM LEAVES OF KNOBWEED (Hyptis capitata Jacq.) - Zuliani, Nur Endah; Erwin, Erwin; Kusuma, Irawan Wijaya (Jurusan Kimia FMIPA UNMUL, 2019)
Test of antioxidant activity of methanol extract and its fractions from leaves of Knobweed (Hyptis capitata Jacq.) were carried out. This research was conducted to determine antioxidant activity in the fractions resulting from column chromatography separation. Antioxidant activity test was carried out by DPPH method while phytochemical was carried out by test colour of TLC method. The results of the first column chromatographic separation produced 18 fractions. The results of the first column antioxidant activity test showed that the value of antioxidant activity ranged from 0.923-81.849% at a sample concentration of 100 ppm. The second column chromatographic separation was carried out in fraction 16. The results of the second column antioxidant activity test produced 18 fractions. The results of the second column antioxidant activity test showed that the value of antioxidant activity ranged from 10.384-59.769% at a sample concentration of 50 ppm. The second column antioxidant activity test produced fraction 15 and fraction 16 showed IC50 values ??of 40.321 and 56.812 ppm respectively. Phytochemical test results showed that fraction 15 and fraction 16 contained alkaloid compounds, flavonoids, polyphenols and steroids/terpenoids. Keywords: Antioxidant, knobweed (Hyptis capitata Jacq), column chromatography, antioxidants, DPPH, secondary metabolites